PENGARUH PEMBERIAN ES KRIM MODISCO TERHADAP KENAIKAN BERAT BADAN PADA BALITA GIZI KURANG - Arolyumna, Anna; Prihatin, Setyo; Subandriani, Dyah Nur (Poltekkes Kemenkes Semarang, 2016)
Background : The intake of nutriens is less than can cause developmental disordes and growth, this causing problebs in malnutrition of children, one of malnutrition based of PSG in Central Java at 2015, the indicator BB/TB prevalence of underweight by 6,9 % and amount to 7,02 % of Semarang. The prevelance of nutrition status in Puskesmas Bangetayu with indicator BB/TB is 11,24 % is the third highest rank on Semarang. One effort to solving problem of underweigth is a gift from PMT is the modisco formula. Hight protein ang energy of ice cream due to addition modisco formula can be alternative snack to children with underweight status. Objective : This study aims to determine the effect of modisco ice cream on stunting to weight gain. Methods :This study is true true experiment with pretest-posttest design with control group. The research subject sebangayk 22 toddlers, consisting of 11 treatment and 11 control, a toddler with malnutrition status indicators BB / TB in Puskesmas Bangetayu. In this study, the treatment was given a modisco ice cream at 100 g for 14days. Results: The mean intake of energy and protein before treatment amounted to 738.86 ± 192.01 kcal and 22.69 g in the treatment group and 1087.12 ± 245.20 kcal and 27.26 g in the control group. The mean intake of energy and protein after treatment amounted to 738.86 ± 192.01 kcal and 27.46 g in the treatment group and 815.3 ± 182.3 kcal and 27.71 g in the control group. Average excess weight of 0.391 kg infants in the treatment group and 0.185 kg in the control group. Conclusion : There is the effect of modisco ice cream to increase weight on underweight of childrean under five with p = 0.01 (p <0.05)